PENELITIAN PERAN PUSTAKAWAN DALAM IMPLEMENTASI KOMPETENSI PEMBELAJARAN SEPANJANG HAYAT MELALUI LITERASI INFORMASI PADA DATABASE GOOGLE CENDEKIA: : SEBUAH NARRATIVE LITERATURE REVIEW - Awaliyah, Shelpi Nur; Anwar, Rully Khairul; Amar, Siti Chaerani Djen; Rukmana, Evi Nursanti (Perpustakaan Nasional RI, 2024)
Lifelong learning is a concept of learning that is carried out continuously in line with human life, because in essence humans are learners. The Library as one of the institutions providing information sources, and reference sources open to all people cannot be separated from the role of librarians in it who play an important role in implementing the concept of lifelong learning in the library. This research aims to find out how the role of librarians in implementing the concept of lifelong learning in the library. This research uses a narrative literature review method from references related to the topic of lifelong learning with the number of references analyzed as many as 4 references from the Google Scholar database. Lifelong learning is a learning process that is carried out continuously, not limited by age, and not limited to formal education. Lifelong learning is closely related to information literacy. Lifelong learning and information literacy are mutually related and support each other in improving people's knowledge and skills. Individuals who have information literacy skills will be more effective in searching, using and evaluating information. Information literacy will provide greater opportunities for individuals to develop their knowledge and skills. Librarians have an important role in the implementation of lifelong learning, one of which is as a provider of learning materials. Mastery of technology, availability of facilities, and the suitability of the program to the needs of the community are things that need to be considered in the implementation of lifelong learning.